Serum cytokine levels and other associated factors as possible immunotherapeutic targets and prognostic indicators for lung cancer - Zhao, Yinghao; Jia, Shengnan; Zhang, Kun; Zhang, Lian (Frontiers in Oncology, 2023)
Lung cancer is one of the most prevalent cancer types and the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) accounts for 80-85% of all cancer incidences. Lung cancer therapy and prognosis largely depend on the disease's degree at the diagnosis time. Cytokines are soluble polypeptides that contribute to cell-to-cell communication, acting paracrine or autocrine on neighboring or distant cells. Cytokines are essential for developing neoplastic growth, but they are also known to operate as biological inducers following cancer therapy. Early indications are that inflammatory cytokines such as IL-6 and IL-8 play a predictive role in lung cancer. Nevertheless, the biological significance of cytokine levels in lung cancer has not yet been investigated. This review's objective was to assess the existing research on serum cytokine levels as a potential immunotherapeutic target and lung cancer prognostic predictor. We hypothesized that changes in serum cytokine levels would forecast the effectiveness of targeted immunotherapy and provide information on the immunological biomarkers for lung cancer.